2021
DOI: 10.3389/feart.2021.667717
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Recurring Seasonal Cycle of Glacier Calving Styles and Patterns

Abstract: Calving is a crucial process for the mass loss of outlet glaciers draining the Greenland ice sheet. Moreover, due to a lack of observations, calving contributes to large uncertainties in current glacier flow models and projections. Here we investigate the frequency, volume and style of calving events by using high-resolution terrestrial radar interferometer (TRI) data from six field campaigns, continuous daily and hourly time-lapse images over 6 years and 10-s time-lapse images recorded during two field campai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…For example, Eqip Sermia (no. 5) had a magnitude of about 290 m and showed very clear terminus-position seasonality (Figure S3) (Kneib-Walter et al, 2021). Glaciers with particularly high magnitudes of terminus-position seasonality include Kangerlussuaq (no.…”
Section: Timing and Magnitude Of Terminus-position Seasonality For Al...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Eqip Sermia (no. 5) had a magnitude of about 290 m and showed very clear terminus-position seasonality (Figure S3) (Kneib-Walter et al, 2021). Glaciers with particularly high magnitudes of terminus-position seasonality include Kangerlussuaq (no.…”
Section: Timing and Magnitude Of Terminus-position Seasonality For Al...mentioning
confidence: 99%
“…However, a number of the glaciers in our study start advancing very late in the season (e.g., December, January) and/or start retreating very early in the season (e.g., February, March) (Figure 3), which suggests that the timing of their seasonality is not entirely controlled by runoff. Instead, the timing of seasonality for these glaciers seems more likely to be controlled by the formation of proglacial mélange, which tends to lag the end of runoff and can facilitate glacier advance (Carr et al, 2013;Howat et al, 2010;Joughin et al, 2008a;Kehrl et al, 2017;Kneib-Walter et al, 2021;Todd and Christoffersen, 2014), and by mid-winter episodes of mélange clearing, which can help initiate early glacier retreat (Cassotto et al, 2015;Joughin et al, 2008a). The conditions under which each mechanism may dominate remain unclear.…”
Section: Timing Of Terminus-position Seasonalitymentioning
confidence: 99%
See 1 more Smart Citation
“…The multidecadal behavior of the terminus positions of marine-terminating outlet glaciers in Greenland is wellcharacterized (Black and Joughin, 2022b;Fahrner et al, 2021;Goliber et al, 2022;Howat and Eddy, 2011;King et al, 2020). Superimposed on these multidecadal trends, many glaciers exhibit seasonal terminus-position variability, which is typically expressed as wintertime advance and summertime retreat (Carr et al, 2013;Cassotto et al, 2015;Fried et al, 2018;Howat et al, 2010;Joughin et al, 2008b;Kehrl et al, 2017;Kneib-Walter et al, 2021;Moon et al, 2015;Murray et al, 2015;Sakakibara and Sugiyama, 2019;Schild and Hamilton, 2013;Seale et al, 2011). Seasonal terminusposition variability spatially varies in amplitude (Fried et al, 2018;Howat et al, 2010;Kehrl et al, 2017;Moon et al, 2015;Seale et al, 2011), and it has been suggested that the amplitude may depend on glacier width (Schild and Hamilton, 2013;Seale et al, 2011) or calving style (Fried et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In front of some glaciers, a rigid mélange tends to form in the winter as sea ice freezes and binds icebergs together. At several glaciers in Greenland, the presence of a rigid mélange in front of a glacier terminus has been shown to inhibit calving and promote glacier advance, and similarly the clearing out or weakening of mélange is associated with glacier retreat (Carr et al, 2013;Cassotto et al, 2015;Fried et al, 2018;Howat et al, 2010;Joughin et al, 2008a;Kehrl et al, 2017;Kneib-Walter et al, 2021;Moon et al, 2015;Todd and Christoffersen, 2014). However, there is not always a clear relationship between mélange and terminus position (Carr et al, 2013;Sakakibara and Sugiyama, 2019).…”
Section: Introductionmentioning
confidence: 99%